(untitled) (Research, Society and Development, 2022)
Currently, there is no effective therapy against Coronavirus disease 2019 (COVID-19). Thus, there is crucial requirement for effective therapy against COVID-19. To our knowledge, few investigations have been conducted on AT2 progenitor cells as target for the (SARS-CoV-2). Hence, alveolar type 2 progenitor cells may be a possible therapeutic agent against COVID19. This review focused on the pathogenesis and pathophysiology of COVID19 disease on AT2 cells and explored potential mechanisms to prevent infection and death of AT2 progenitor cells as possible therapy against COVID-19. We propose that inhibition of IL-1 receptor, IL 1, NFkB and JNK signalling pathway may serve as therapeutic target for COVID-19